Exploring Metaphors in the Lyrics of Sia's Album “1000 Forms of Fear” - Aisyah, Siti; Wibowo , Hanafi (English Language Teaching Prima Journal (ELT), 2024)
This research explores the role of metaphor in the lyrics of Sia's 1000 Forms of Fear album, examining how figurative language enhances the emotional and conceptual effects of the songs. Using a qualitative methodology, this study classifies metaphors into ontological, structural, and orientational categories according to Lakoff and Johnson's framework. The results reveal the dominance of ontological metaphors, which transform abstract feelings into concrete experiences, allowing listeners to engage deeply with themes of resilience, vulnerability, and mental challenges. The research emphasizes the cognitive and emotional role of metaphors in music, illustrating how metaphors assist listeners in understanding complex feelings and stories. The study highlights that metaphorical language in music not only deepens lyrical content but also enhances emotional resonance, ultimately expanding our understanding of the function of music in conveying complex human experiences.